Estudio reológico de tres bebidas fermentadas de yuca “(manihot esculenta crantz)” con kéfir y levadura. - Laura Tiban, Wilmer Javier (2021)
The present research work determined the rheological study of three fermented cassava beverages for this purpose three best treatments were identified by means of physical-chemical analysis (alcoholic degrees, ºBrix, pH and acidity), the data were obtained at 24, 48 and 72 hours of storage for this purpose an experimental design was applied with a 3x2x2 factorial arrangement with 2 repetitions under a DBCA, where the study factors were: Factor A (Conditioning), Factor B (Temperature), Factor C (Type of container) with 12 treatments, the response variables were evaluated in Infostat giving as a result for white chicha - 18 ºC - glass container, acidity of 0.13 % ac. Lactic acidity, 1.8 ºBrix, 1.0 alcoholic content and 5.02 pH, chicha wiwis - 18 ºC - glass container, acidity of 0.6% lactic acidity, 3.0 ºBrix, 1.7 alcoholic content and 3.89 pH and chicha negra - 18 ºC - glass container, acidity of 0.46% lactic acidity, 3.6 ºBrix, 1.9 alcoholic content and 4.44 pH. For the rheological study of three fermented beverages, a Brookfield rotational viscometer of the laboratory (La Conal, Setlab) was used with the L1 spindle of length 62 mm and radius 15 mm at 0.6 - 30 and 40 rpm. Calculations were performed using the "Ostwald de Wael" power equation to obtain the shear stress () and strain rate (y), with this by linear regression between ln(2πN/60) versus ln(τ) the rheological index (n) was obtained, for the consistency index (K) was obtained with logarithmic regression Log (y) versus Log (τ) and for the apparent viscosity profile μa (Pa.s) was performed with the equation (Sharma and Mulnaney). The evaluation of each treatment was done at temperatures of 18°C for white chicha and chicha wiwis and 25°C for black chicha. The results for white chicha were rheological index n= 0.124 dimensionless, consistency index K= 0.34 Pa.sn, apparent viscosity (μa) (Pa.s), a count of <10 CFU/cm3 in molds, <10 CFU/cm3 in enterobacteria and 1.22 x102 CFU/cm3 in yeasts, nutritional values of protein 2.97 %, fiber 0.91 %, fat 0.05%, calcium 0.031 % and potassium (0.17 %). The chicha wiwis the rheological index n= 0.071 dimensionless, consistency index K= 0.189 Pa.sn, apparent viscosity (μa) (Pa.s), a count of <10 CFU/cm3 in molds, <10 CFU/cm3 in enterobacteria and 1.45 x102 CFU/cm3 in yeasts, nutritional values in protein 2.23 %, fiber 0.67 %, fat 0.07 %, calcium 0.053 % and potassium 0.29 %. The black chicha rheological index n= 0.047 dimensionless, consistency index K= 0.184 Pa.sn, apparent viscosity (μa) (Pa. s), a count of <10 CFU/cm3 in molds, <10 CFU/cm3 in enterobacteria and 1x102 CFU/cm3 in yeasts, protein (2.65%), (fiber 0.80%), fat (0.04%), calcium (0.011%) and potassium (0.071%). The three cassava drinks did not show any difference in the rheological index typical of a fluid with pseudoplastic characteristics n>0. The rheogram of the beverages were fitted with a coefficient of determination above 99%. The power law model described the rheological behavior.